Open access data platforms as research tools: an incomplete academic task in the Cuban context - Mayelín Mirabal Sosa; Armando Humberto Seuc JO; Yanet García Serrano; Karen Alfonso Sagué; Darily Losada Gandarilla; Carlos Moncada Menéndez (Medisur)
The state of open access in Cuba is reviewed, in relation to bibliographic databases and other databases and metadata. Emphasis is placed on the importance of open access to databases in general, particularly those generated by epidemiological research of national scope. The possible reasons why this area is insufficiently developed in our country are discussed. The use of different international data platforms is illustrated, which allows our researchers to access considerable volumes of data and their pertinent analysis.